Impact of Costa Rica's Program of Payments for Environmental Services on Land Use - Sills, Erin; Arriagada, Rodrigo; Ferraro, Paul; Pattanayak, Subhrendu; Carrasco, Luis; Ortiz, Edgar; Cordero, Silvia; Caldwell, Katie; Andam, Kwaw (World Bank, Washington, DC, 2014)
Costa Rica's Program of Payments for Environmental Services (Pago de Servicios Ambientales, PSA) provides a unique opportunity to evaluate direct payments as a conservation policy tool. This paper reports evidence on how much more forest has been conserved in Costa Rica as a result of PSA contracts with landowners. Such evidence requires estimating a counterfactual outcome: how much forest would have been preserved if there had been no payments. By applying rigorous program evaluation methods that have been recommended for identifying the causal effects of conservation policies, we find that the PSA program does result in a small but statistically significant increase in the area of forest conserved.